A transporter of 1‐aminocyclopropane‐1‐carboxylic acid affects thallus growth and fertility in Marchantia polymorpha. Issue 6 (19th October 2022) - Li, Dongdong; Dierschke, Tom; Roden, Stijn; Chen, Kunsong; Bowman, John L.; Chang, Caren; Van de Poel, Bram
Summary: In seed plants, 1‐aminocyclopropane‐1‐carboxylic acid (ACC) is the precursor of the plant hormone ethylene but also has ethylene‐independent signaling roles. Nonseed plants produce ACC but do not efficiently convert it to ethylene. In Arabidopsis thaliana, ACC is transported by amino acid transporters, LYSINE HISTIDINE TRANSPORTER 1 (LHT1) and LHT2. In nonseed plants, LHT homologs have been uncharacterized. Here, we isolated an ACC‐insensitive mutant (Mp ain ) that is defective in ACC uptake in the liverwort Marchantia polymorpha . Mp ain contained a frameshift mutation (1 bp deletion) in the Mp LHT1 coding sequence, and was complemented by expression of a wild‐type Mp LHT1 transgene. Additionally, ACC insensitivity was re‐created in CRISPR/Cas9‐Mp lht1 knockout mutants. We found that MpLHT1 can also transport l ‐hydroxyproline and l ‐histidine. We examined the physiological functions of Mp LHT1 in vegetative growth and reproduction based on mutant phenotypes. Mp ain and Mp lht1 plants were smaller and developed fewer gemmae cups compared to wild‐type plants. Mp lht1 mutants also had reduced fertility, and archegoniophores displayed early senescence. These findings reveal that MpLHT1 serves as an ACC and amino acid transporter in M. polymorpha and has diverse physiological functions. We propose that MpLHT1 contributes to homeostasis of ACC and other amino acids in M. polymorpha growth and reproduction.